Fortification and bioavailability of zinc in potato - Vergara Carmona, Victor M [UNESP]; Cecílio Filho, Arthur B [UNESP]; Almeida, Hilário J de [UNESP]; Gratão, Priscila Lupino [UNESP] (Wiley, 2019)
BACKGROUND: Most agricultural soils have low zinc (Zn) content available to crops, which results in a significant decrease in productivity and in public health problems. However, the priming of potato tubers in solutions with Zn can be an effective strategy for their fortification. In order to evaluate the effect of Zn concentrations and tuber priming time on the fortification and bioavailability of Zn, potato tubers were primed in solutions containing 0, 10, 20 and 30 mg mL −1 Zn during 12, 16, 20, and 24 h, respectively. The dry matter and the content of Zn and phytic acid (PA) in tubers were assessed in order to obtain the PA:Zn molar ratio. RESULTS: Longer priming time increased the Zn content in the cortex of the tubers. High Zn concentration in the solution increased the content of Zn linearly in both the cortex and the central region of the tuber, whereas in the periderm the content levels adjusted to the non-linear logistical model, showing saturation at a minimum of 10 mg mL −1 Zn in the solution. An increase in the bioavailability of Zn was verified when there was higher Zn concentration in the solution. CONCLUSION: A substantial increase in Zn bioavailability was obtained by priming the tubers for 12 h in 10 mg mL −1 Zn. © 2019 Society of Chemical Industry.
Keywords: biofortification; micronutrient; phytic acid; Solanum tuberosum L